Bathyal benthic habitats from the southern Apulian slope: characterization, spatial distribution and modifications through time - VERTINO, AGOSTINA VALERIA; SAVINI, ALESSANDRA; NEGRI, MAURO PIETRO; MALINVERNO, ELISA; CORSELLI, CESARE; Beuck, L; Mastrototaro, F (2011)
The examined bathyal area, ranging from about 300 to 1100 m water depth, is located along the southern Apulian continental slope. It includes the so-called Cold-Water Coral (CWC) Mound Province of Santa Maria di Leuca and is characterized by three main physiographic domains: from east to west (1) a large mass-transport deposition area where mound-like features occur, (2) a prominent ridge covered by sparse debris deposits where drift sedimentation is documented, and (3) a series of narrow ridges and fault scarps that outline large erosive features (e.g., canyons). The analysis of videos, samples and acoustic facies from ten selected sites shows that both live and dead CWCs (mostly represented by the scleractinian species Madrepora oculata, Lophelia pertusa and Desmophyllum dianthus) occur in all three domains. In particular, video and sample analyses have allowed us to distinguish three main habitat groups (coral-, hardground- and muddominated habitats) which contain diverse subhabitats, generally grading into each other. By combining sample/video data with acoustic facies, we can assert that (a) extensive coral thickets, formed by dead and live colonies of M. oculata and L. pertusa, characterize the upper part of several mound-like structures of the eastern sector and, most probably, the top of elongated ridges from the western sector, (b) small-scale bioconstructions, dominated by the solitary gregarious species D. dianthus, preferentially occur along subvertical and overhanging walls of the western sector, (c) mud-dominated facies are spread on horizontal to gently sloping bottoms of all three sectors. Our study highlights a significant spatial heterogeneity of the bathyal benthic habitats from the southern Apulian slope. This seems to well reflect the complexity of variable geomorphic and/or hydrographic processes acting upon the slope. Moreover, remarkable variations of skeletonized faunal assemblages, observed along several sediment cores (from 30 to 150 cm long), reveal that benthic communities have been ...